HUBUNGAN ANTARA PERILAKU MEROKOK ORANG TUA DAN ANGGOTA KELUARGA YANG TINGGAL DALAM SATU RUMAH DENGAN KEJADIAN ISPA PADA BALITA DI WILAYAH KERJA PUSKESMAS SEMPOR II KABUPATEN KEBUMEN TAHUN 2009 - -, winarni; ummah, Basirun al; ANS, safrudin (Jurnal Ilmiah Kesehatan Keperawatan, 2010)
Acute respiratory tract infection mostly occurred on children in develop or modern countries. Most of them need a special treatment at hospital and sometimes, patients develop emergency situation.  The huge number of smoking behaviour of parents, it will have bad impact to their children. Smoking parents’ behaviour in the long time could cause acute respiratory tract infection to their children. The aim of this study is to find out of smoking parents behaviour to incidence of acute respiratory tract infection to their children under five years old. The type of the research was used to test independent and dependent variables. There was 65 respondents were used purposive sampling method.The data were analyzed by using chi square to find out the correlation between parent smoking behaviour and others family in a home with ISPA occurrence of children. Research finding showed that p=0.000 with the significance level (p<0.05),  there was correlation between parent smoking behaviour and others family in a home with ISPA occurrence of children under five years old in Sempor II community health centre (Puskesmas) work area, Kebumen Regency on 2009.   Keywords: smooking behavior, parent, acute respiratory tract infection, children under five year